Практичні аспекти застосування матриці бостонської консультативної групи - Крайнюченко (Форноляк), Ольга Феодосіївна; Бєлова, Тетяна Геннадіївна; Гаврилова, Тетяна Василівна (My University, 2012)
Розглянуто особливості практичного застосування матриці Бостон консалтинг груп, її переваги та недоліки; проведено аналіз обґрунтованості результатів отриманих за адаптованою матрицею БКГ та, як наслідок, розроблено та запроваджено до застосування модифіковану матрицю БКГ як різновид класичного її варіанту; удосконалено методику оцінювання ступеню збалансованості товарного портфеля підприємства. Researches of the article is conducted relatively of practical questions of application of classic matrix of the Boston Consulting Group and validity of the use of its variety – the adapted matrix. These researches are reflected, that efficiency of application of this matrix in the situation of irrationality of structure of commodity assortment goes down considerably. As a result has been offered to using the modified matrix BCG for the scientific researches and practical activity of enterprises. Basis of construction of matrix are indexes of «rates of growth of volumes of sales of strategic production units » and «profitability of strategic production units». In the article were considered the questions of interpretation of results of researches on the basis of varieties of matrix BCG. . As a result has been offered improved method of estimation of
Keywords: стратегічний аналіз; консалтинг; асортиментний портфель; товарна політика; strategic analysis; consulting; кафедра маркетингу